2017
DOI: 10.1520/gtj20160227
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Clayey Soil with Garlic Skin and Rice Husk Ash for Flexible Pavement Construction

Abstract: Soil stabilization is the method of improving the strength characteristics of in situ soil by compaction or by the addition of admixtures. Clay minerals have small particles and a variable degree of crystal perfection. Therefore, construction on clayey soil is really an arduous job due to low strength and swelling problems. In this paper, an attempt is made to determine the improvement in geotechnical characteristics of locally available clayey soil by adding garlic skin and rice husk ash (RHA) as admixtures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Improvement of weak soil by using various industrial by-products is a well-established practice worldwide. Several studies have successfully shown the significance of using different industrial by-products like marble dust [22,23], glass dust, blast furnace slag [24,25], rice husk ash [26], sugar cane waste, fly ash [27,28], coal ash [29], xanthan gum [30], etc., for soil improvement. As phase-2 of this research, the possibility of stabilization of leachate contaminated cohesive soils (CL-dyeing, CL-tannery, CH-dyeing and CH-tannery) using marble dust and ground granulated blast furnace slag (GGBFS) was explored.…”
Section: Effect Of Industrial By-products On Leachate Contaminated Soilsmentioning
confidence: 99%
“…Improvement of weak soil by using various industrial by-products is a well-established practice worldwide. Several studies have successfully shown the significance of using different industrial by-products like marble dust [22,23], glass dust, blast furnace slag [24,25], rice husk ash [26], sugar cane waste, fly ash [27,28], coal ash [29], xanthan gum [30], etc., for soil improvement. As phase-2 of this research, the possibility of stabilization of leachate contaminated cohesive soils (CL-dyeing, CL-tannery, CH-dyeing and CH-tannery) using marble dust and ground granulated blast furnace slag (GGBFS) was explored.…”
Section: Effect Of Industrial By-products On Leachate Contaminated Soilsmentioning
confidence: 99%
“…e macroscopic mechanical properties of soil essentially depend on its microstructure, so studying soil microstructure characteristics helps to better understand the mechanism of strength improvement [34,35]. Some scholars have used different microscopic methods to study the microstructure characteristics of soil or stabilized soil, including scanning electron microscopy (SEM) [36][37][38][39][40], mercury intrusion porosimetry (MIP) [41][42][43], energy dispersive X-ray spectroscopy (EDS) [44][45][46], and X-ray diffraction [25,47]. Using microscopic technology to study soil microscopic properties has become quite popular and mature.…”
Section: Introductionmentioning
confidence: 99%
“…Com base nos autores já citados, percebe-se que a estabilização de solos representa um melhoramento das caracterisiticas fisicas e mecânicas dos solos, atraves das misturas, sejam com outros solos, com agregados ou outros materiais estabilizantes, permitindo que o meterial estabilizado obtenha uma estabilidade e durabilidade adequada (JAISWAL & LAL 2017;OLIVEIRA et al, 2019).…”
Section: Introductionunclassified